Lesson Study as a Means for Facilitating Preservice Teacher Reflectivity - Julia Myers (International Journal for the Scholarship of Teaching and Learning, 2012)
This study sought to determine if, how, and the extent to which, the implementation of lesson study with preservice teachers facilitates reflection in its participants. The lesson study reports of 20 preservice teachers were analyzed qualitatively along three dimensions to determine what lesson study reports revealed about their reflections. More specifically, the analysis sought to determine what preservice teachers wrote about in their lesson study reports, and if it showed signs of reflectivity. The analysis revealed that the reflections of the participants, as evidenced within lesson study reports, resided at the lowest levels, thus supporting existing literature on the reflective abilities of preservice teachers. It also highlighted the difficulty of determining the degree to which individuals engage in reflective thinking. The results point to several considerations for those who wish to implement lesson study with preservice teachers, and identify numerous questions that warrant further investigation.